Kalite iyileştirilmesinde istatistiksel yöntemler - Çoban, Güler (My University, 2003)
Bir ürün veya hizmetin, tanımlanan veya talep edilen ihtiyaçları tatmin etme yeteneğini gösteren özellik veya karakteristiklerinin toplamı olarak tanımlanabilen kalite, günümüzün serbest rekabet ortamında, firmaların hatta ülkelerin ekonomik aktivitelerinde başarıya ulaşmalarında kilit rolü oynamaktadır. Kalite sürekli değişen ve en iyiye doğru giden bir kavramdır. İnsanoğlunun beklentileri ve teknolojideki gelişmeler sürdükçe kalite de sürekli gelişmek ihtiyacındadır. Kalite iyileştirme çalışmaları ve mevcut olan süreç geliştirmesi için problemler ve oluşum yerleri belirlenmeli, daha sonra giderilmesi ve daha başka problemlerin oluşmasının önlenmesi için tedbirler uygulanmalıdır. İstatistiksel yöntemler üretim sürecinin iyileştirilmesi ve kusurlu üretimin azaltılması için kullanılan etkili araçlardır. Ancak, istatistiksel araçların yalnızca 'araç' oldukları ve uygun bir şekilde kullanılmadıklarında amaca hizmet etmeyecekleri unutulmamalıdır. Önemli olan hangi aracı hangi durumda kullanmamamız gerektiğini bilmek ve bunlar ışığında doğru kararlar vererek uygulamaya geçmektir. The sum of the features or the characteristics of the abilities that satisfy defined or demanded needs of the product or the service is explained as the quality. In today's free competing area for the companies even for the countries in their economic activities, quality has the key role which serves for success. Quality is a concept that is continually changeable and goes towards the best. As the human beings' expectations and the advancement in the technology continue to appear, quality always needs to develop. For this matter of quality improvement and existing process' development searches for appropriate methods appear. For the work of quality improvement, problems and their places of formation will be determined, later they will be removed and the formation of more problems will be prevented as there will be providences. Statistical methods are the effective tools for the improvement of the production process and the decrease that appear in the faulty production. However, statistical tools are the only tools and if they are not used appropriately, it will not be forgotten that they can not serve for their aims. The most important thing is knowing the tools which will not be used in some situations and with the enlightenment of previous information about disuse, by giving true decisions the applications will be done.
Keywords: Kalite Yönetimi